EXPLORING EFL STUDENTS' PERCEPTIONS AND CHALLENGES IN INTEGRATING RECIPROCAL TEACHING AND COMMUNICATIVE LANGUAGE TEACHING - Krismayani, Ni Wayan Krismayani; Budiarta, I Komang; Hartika, Ni Putu Leyen; Mahottami, Ni Komang Aryanti; Sawitri, Ni Luh Putu Dian (Jurnal Santiaji Pendidikan (JSP), 2025)
In today's global world, reading and speaking English well is a key skill for helping students do well in class. Learning methods can affect how well students learn in places where English is a foreign language (EFL). This study aims to determine how EFL students feel about and deal with the difficulties of combining two popular language teaching methods, Reciprocal Teaching (RT) and Communicative Language Teaching (CLT), in higher education institutions. A mixed-methods approach was used to gather data from English Language Education Study Program students. This included observations, questionnaires, and interviews. The results show that most students think combining RT and CLT is a good way to help them understand what they read, speak fluently, and learn with others. RT strategies help make predictions, ask questions, clarify, and summarize texts. CLT, on the other hand, promotes real-life communication activities like group discussions and role-playing. Students also expressed a preference for interactive, contextual, and collaborative learning. But this study also found several challenges, such as insufficient time to learn, anxiety when speaking and a tendency for some students to prefer independent learning. Cultural factors, learning styles, and support affect students' involvement and reactions to both approaches. These findings contribute to developing more effective, student-centred, and relevant English language learning.